2018
DOI: 10.1002/ps.4801
|View full text |Cite
|
Sign up to set email alerts
|

Alternative control of Aedes aegypti resistant to pyrethroids: lethal and sublethal effects of monoterpene bioinsecticides

Abstract: This study highlights the potential of the essential oil of A. trilobata and its major compounds ρ-cymene and limonene for the control of A. aegypti and reveals the importance of analyzing sublethal effects on the population dynamics of the A. aegypti mosquito. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 48 publications
3
10
0
1
Order By: Relevance
“…Significant percentages of other constituents were also identified, such as spathulenol (6.68% ± 0.15%), viridiflorene (4.23% ± 0.17%), β-caryophyllene (4.01% ± 0.22%), and limonene (3.75% ± 0.07%). The occurrence of sulcatyl acetate as the major constituent of A. trilobata oil is in agreement with data reported by Santos et al (2014) (23.31% ± 0.28%) and Silva et al (2018) (25.64% ± 0.45%), who also found this compound to be the major constituent in oils from this species.…”
Section: Ethics Statementsupporting
confidence: 92%
See 1 more Smart Citation
“…Significant percentages of other constituents were also identified, such as spathulenol (6.68% ± 0.15%), viridiflorene (4.23% ± 0.17%), β-caryophyllene (4.01% ± 0.22%), and limonene (3.75% ± 0.07%). The occurrence of sulcatyl acetate as the major constituent of A. trilobata oil is in agreement with data reported by Santos et al (2014) (23.31% ± 0.28%) and Silva et al (2018) (25.64% ± 0.45%), who also found this compound to be the major constituent in oils from this species.…”
Section: Ethics Statementsupporting
confidence: 92%
“…A previous investigation of the chemical profile of the essential oil from A. trilobata occurring in the Caatinga biome of northeastern Brazil revealed sulcatyl acetate (6-methyl-5-hepten-2-yl acetate) as the main component, followed by limonene, linalool, and p-cymene (Santos et al 2014). Moreover, an evaluation of its insecticidal activity demonstrated that this oil is an excellent alternative for use in controlling Aedes aegypti L. larvae and adults (Silva et al 2018). Recently, Oliveira et al (2017) found that both the oil and its main component exhibited fast, efficient activity against Atta sexdens L. and Acromyrmex balzani Emery through fumigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, essential oils are also known to cause a variety of sublethal effects that are detrimental to insect survival and reproduction. These effects include repellency, irritability, altered respiratory activity, changes in swimming pattern, and reduced adult emergence, longevity, fertility, fecundity and natality [49][50][51][52]. Future studies evaluating both the lethal and sublethal effects of L. scoparium essential oil, its fractions and emulsions could reveal the full spectrum of their biological effects against mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of insecticides can have sublethal effects on insects and are often involved in the development of insecticide resistance [8,9,10]. Sublethal effects of insecticides can inhibit or stimulate the growth of insect populations via their effects on development, survival, and reproduction rate of insects, which vary according to the species and the insecticide used [11,12,13].…”
Section: Introductionmentioning
confidence: 99%